2014
DOI: 10.1007/s00436-014-4067-6
|View full text |Cite
|
Sign up to set email alerts
|

Animal model of human disease with optic neuritis: neuropapillitis in a rat model infected with Angiostrongylus cantonensis

Abstract: Human Angiostrongylus cantonensis (A. cantonensis) is a food-borne parasitic disease and can cause optic neuritis. Increasing clinical angiostrongyliasis cases with optic neuritis have been reported, but the pathogenesis has not been fully understood until now. Here, we applied rats with A. cantonensis infection as an animal model to study the pathogenesis of optic neuritis caused by the infection. We observed that the optic disk of experimental rats appeared hyperemic, the retina vein became thick, and the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The third-stage larvae of A.cantonensis were obtained from the infected Amazonian snail ( Ampullaria gigas ) by digestion of the snail tissue in artificial gastric juice (0.3 % pepsin, 0.7 % HCL and 10 ml/g tissue) at 37 °C for 2 h. The precipitates were then washed with distilled water, and the third-stage larvae were counted and collected by microscopy [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The third-stage larvae of A.cantonensis were obtained from the infected Amazonian snail ( Ampullaria gigas ) by digestion of the snail tissue in artificial gastric juice (0.3 % pepsin, 0.7 % HCL and 10 ml/g tissue) at 37 °C for 2 h. The precipitates were then washed with distilled water, and the third-stage larvae were counted and collected by microscopy [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some surveys showed that anti-inflammation or anti-helminthic treatment had no obvious effect on demyelination caused by A. cantonensis . We therefore investigated the impact of TSIIA combined with AB 2, 3 on demyelination caused by A. cantonensis . Previous studies showed that TSIIA can protect neurons from damage, including ganglion cells, dopaminergic neurons, hippocampal neurons, and cortical neurons 21-24.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously shown that A. cantonensis infection leads to obvious demyelination of CNS in BALB/c mice 1, 2. Previous studies revealed that anti-helminthic treatment alone or in combination with corticosteroids had no obvious effect on demyelination caused by A. cantonensis 2, 3, suggesting that simple antiparasitic or/and suppression of inflammation is not sufficient . It is therefore necessary to identify more efficient treatment strategies to prevent demyelination associated with angiostrongyliasis.…”
Section: Introductionmentioning
confidence: 89%
“…These findings underscore the need to identify more detailed pathogenesis. Infiltration of lymphocytes, macrophages, eosinophils and neutrophils is the dominant pathogenic manifestation of infected brain, not only that, demyelination is a typical injury which brings out limitation of nerve impulse conduction in which animal motor function is bound to be impacted [2,3,4].…”
Section: Introductionmentioning
confidence: 99%